E-Module Development Based on Flip PDF Professional by Using Problem Solving Model in Wetland Context to Improve Stoichiometry Learning Outcomes - Iriani Bakti; Rilia Iriani*; Anisa Ihdayanti; Abdul Hamid (Jurnal Pendidikan Sains Indonesia, 2023)
E-module development based on flip pdf professional is a systematically arranged instructional material. This research aimed to determine the impact of student learning outcomes when using the developed e-module. The research method used is R D with a 4-D development model: define, design, develop and disseminate. The developed e-module trial was conducted offline for students at SMAN 10 Banjarmasin. The data analysis technique was descriptive statistics. The data collection techniques were validation sheets, response questionnaires and test assessments. The results showed that the developed e-module was stated to be very valid regarding the content feasibility, presentation, language and media. The developed e-module also fulfills practical aspects, seen from student response questionnaires and teacher activity sheets which get very good categories. The e-module also fulfilled the effectiveness aspect based on the N-gain of student learning outcomes included average category. The success of e-module in improving learning outcomes can also be seen from the increased average value pre-test and post-test, from 43.75 to 83.75. The results of the research show that the developed e-module is feasible to use and also improves learning outcomes